1969
DOI: 10.1039/tf9696501891
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic oxidation of methane on zeolites containing rhodium, iridium, palladium and platinum

Abstract: The complete oxidation of methane over zeolites containing palladium, platinum, rhodium and iridium has been studied using a microcalorimetric technique. The results show that isolated ions of these metals are able to adsorb both methane and oxygen but only with platinum do methane and oxygen adsorb competitively. The activation energies for the reaction show that the rate-determining step is the same on each catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Rh is far less studied for CH 4 oxidation, , but it is an important component of the three-way catalyst, where it yields improved catalytic activity and stability. , Here, we report that a rhodium-based 2 wt % Rh/ZSM-5 catalyst can achieve high methane conversion at practically achievable temperatures and high space velocities even in the combined presence of H 2 O and SO 2 . Although the high cost of Rh should be considered, when evaluating the business case for Rh catalysts, the identification of a catalyst that provides high conversion at realistically achievable conditions is a fundamental advance that shows great promise for the development of solutions to the methane slip problem.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Rh is far less studied for CH 4 oxidation, , but it is an important component of the three-way catalyst, where it yields improved catalytic activity and stability. , Here, we report that a rhodium-based 2 wt % Rh/ZSM-5 catalyst can achieve high methane conversion at practically achievable temperatures and high space velocities even in the combined presence of H 2 O and SO 2 . Although the high cost of Rh should be considered, when evaluating the business case for Rh catalysts, the identification of a catalyst that provides high conversion at realistically achievable conditions is a fundamental advance that shows great promise for the development of solutions to the methane slip problem.…”
Section: Introductionmentioning
confidence: 81%
“…Whereas Pdbased catalysts are relatively sulfur-tolerant under dry conditions, 28,29 the simultaneous presence of H 2 O and SO 2 causes a severe inhibition of the catalytic activity. 18,30 Rh is far less studied for CH 4 oxidation, 31,32 but it is an important component of the three-way catalyst, where it yields improved catalytic activity and stability. 33,34 Here, we report that a rhodium-based 2 wt % Rh/ZSM-5 catalyst can achieve high methane conversion at practically achievable temperatures and high space velocities even in the combined presence of H 2 O and SO 2 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several studies of the catalytic decomposition of nitrous oxide have been reported recently (77,27,29,85). In a study on a series of oxides with the general formula M2Os (35), mostly rare-earth oxides, the kinetics were described by a rate law of the form It w-as concluded that desorption of oxygen is the rate-limiting step' in the sequence N20 ;=± N20 (ads) N20 (ads) + e--* N20" (ads) N20" (ads) -0~( ads) + N2 The apparent activation energies and preexponential factors for the various oxides show a strong correlation with the corresponding kinetic parameters for the isotopic exchange reaction of ls02 with the oxide surfaces.…”
Section: Reactions Of Nitrogen Oxidesmentioning
confidence: 99%